2014
DOI: 10.1117/12.2050356
|View full text |Cite
|
Sign up to set email alerts
|

Understanding differences between healthy swallows and penetration-aspiration swallows via compressive sensing of tri-axial swallowing accelerometry signals

Abstract: Swallowing accelerometry is a promising tool for non-invasive assessment of swallowing difficulties. A recent contribution showed that swallowing accelerometry signals for healthy swallows and swallows indicating laryngeal penetration or tracheal aspiration have different time-frequency structures, which may be problematic for compressive sensing schemes based on time-frequency dictionaries. In this paper, we examined the effects of different swallows on the accuracy of a compressive sensing scheme based on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Noninvasive swallowing study cannot replace VFSS. The noninvasive swallowing study was developed to complete the information obtained from analysis with VFSS [10,35,36,[40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive swallowing study cannot replace VFSS. The noninvasive swallowing study was developed to complete the information obtained from analysis with VFSS [10,35,36,[40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…100,[103][104][105] Due to its inaccuracy, research has demonstrated the risk of using CA as a stand-alone tool for assessing dysphagia. 97,101,103,104,[106][107][108][109] Comparing healthy swallows and penetration-aspiration swallows with a tri-axial accelerometer, Sejdic et al showed that each axis (three anatomical directions) reported distinct information. 97 This finding suggests that the position and orientation of a sensor influence the recorded signal.…”
Section: Possible Added Value Of Acoustic Coughrelated Features In Hnc-patients With Late Radiationassociated Dysphagiamentioning
confidence: 99%
“…97,101,103,104,[106][107][108][109] Comparing healthy swallows and penetration-aspiration swallows with a tri-axial accelerometer, Sejdic et al showed that each axis (three anatomical directions) reported distinct information. 97 This finding suggests that the position and orientation of a sensor influence the recorded signal. Movahedi et al have demonstrated that recordings with distinct transducers (microphones and accelerometers) are idiosyncratic and non-interchangeable.…”
Section: Possible Added Value Of Acoustic Coughrelated Features In Hnc-patients With Late Radiationassociated Dysphagiamentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 As these signals are K-sparse signals, we proposed a compressive sensing (CS) approach such that a discrete-time signal of dimension N is encoded by computing a measurement vector y that consists of M ≪ N linear projections of the vector s :…”
Section: Compressive Sensing Of Tri-axial Swallowing Accelerometrymentioning
confidence: 99%